Treatment of Male Sexual Partners of Women With Bacterial Vaginosis: A Randomized, Double-Blind, Placebo-Controlled Trial. (31st December 2020) - Schwebke, Jane R; Lensing, Shelly Y; Lee, Jeannette; Muzny, Christina A; Pontius, Angela; Woznicki, Nicole; Aguin, Tina; Sobel, Jack D
Abstract: Background: We aimed to determine if treatment of male sexual partners of women with recurrent bacterial vaginosis (BV) with oral metronidazole 2×/day for 7 days (ie, multidose metronidazole) significantly decreased BV recurrence rates in the female. Methods: This was a multicenter, 2-arm, double-blind, placebo-controlled study. Women with recurrent BV and current diagnosis of BV by Amsel and Nugent were enrolled. Multidose metronidazole for 7 days was dispensed to women. Male partners were randomized to placebo versus multidose metronidazole for 7 days and asked to refrain from unprotected sex for 14 days. Female follow-up visits were conducted at day 21 and 8 and 16 weeks. Male follow-up visits occurred at days 14–21. BV cure was defined as 0–2 Amsel criteria and Nugent score 0–6 in the female partner with the primary endpoint at 16 weeks. Results: 214 couples were enrolled. In the intent-to-treat population, there was no significant difference between treatment arms for the primary outcome. BV treatment failure occurred in 81% and 80% of women in the metronidazole and placebo arms through the third follow-up visit, respectively ( P > .999). However, women whose male partners adhered to study medication were less likely to fail treatment (adjusted relative risk, .85; 95% CI, .73–.99; P = .035). This finding persisted in post hoc comparisons in the metronidazole arm. Conclusions: Overall, this study did not find that male partner treatment with multidose metronidazole significantly reduces BV recurrence in female partners, although women whose partners adhered to multidose metronidazole were less likely to fail treatment. Clinical Trials Registration: (NCT02209519). Abstract : Treatment of the male sexual partner with oral metronidazole 500 mg 2×/day for 7 days showed no effect on bacterial vaginosis recurrence in the female. However, women whose partners were adherent to multidose metronidazole were less likely to fail treatment.